Concurrent mapping of an adenovirus 5/SV40 integration site and the U1 snRNA cluster (RNU1) within 400 kb of the chromosome region 1p36.1. - Romani, M; Baldini, A; Volpi, E; Casciano, I; Nobile, C; Muresu, R; Siniscalco, M (1994)
Previous reports from our group suggested the preferential integration of the viral construct Ad5/SV40 at the short arm subtelomeric region of human chromosome 1. The present study narrows the region of viral integration to site 1p36.1 in a close cytogenetic overlap with the U1 snRNA gene cluster (RNU1) within a distance necessarily smaller than 400 kb as suggested by the size of the YAC in which the two markers were found to coexist. This finding supports the hypothesis that the chromosomal site in question may have a constitutional propensity to genetic recombination.